Real Ugly, Dead Beautiful - Raymond Ryan (Oz, 1998)
In the early 1980s, the all-girl band "The Same" used to play around New York City, piecing together lyrics from fragments of various languages. In that cauldron of fashion and media, "The Same" had the memorable motto Semper Mutans (Always Changing).